PENYELENGGARAAN PROGRAM PPL PADA PERGURUAN TINGGI LPTK - Mada Sutapa; Agus Timan; Ahmad Yusuf Sobri (Universitas Pendidikan Indonesia, 2020)
This study aims to describe the implementation of the PPL program and analyzing problems in the implementation in the field. The research was conducted using case studies in the implementation of the PPL program in the Education Management Study Program (MP) Yogyakarta State University (UNY). Data collection is done by observation, interview, and document study. The results of the study show that: The use of Nomenclature for Course Introduction in School Field (PLP) raises problems during the implementation of field experience practice programs, related to Siakad, and perceptions of institutions where MPs study practice. The practice patterns of MP Study Program activities are carried out continuously and are interrelated between Pre PPL, OLMP activities, Educational Internship activities, and Post PPL; Problems in conducting PPL programs are related to the absence of a formal PPL Program Guide; and Collaborative guidance has not yet been fully carried. Research recommendations, that Naming the nomenclature of field practice subjects that have been standardized in academic regulations to become an Introduction to School Field (PLP) needs to be reformulated by considering non teacher training programs, by not eliminating scientific substance; and Collaborative guidance needs to be carried out for the successful practice of field experience between study programs, DPLs, and civil service staff in practice institutions.